Resignifying the nonplace during the pandemic (COVID-19): men, women, and children on street situation in São José dos Campos/SP, Brazil - Goulart Silva, Marília; Maria Maciel, Lidiane; Moreira de Souza, Adriane Aparecida (Geografares, 2021)
This article has as its theme the territoriality of the homeless population during the COVID-19 pandemic. The main objective is to point out issues regarding the condition experienced by homeless people in the city of São José dos Campos / SP, considering the use of public spaces as a means of survival. A discussion about the “non-place” based on Marc Augé's theory is proposed in the light of an ethnographic analysis of the places occupied by these people living on the street. The final considerations of this article indicate a new meaning for spaces used by the homeless population, especially public spaces, such as streets, bus stations and squares. It appears that these men, women and children act in a way to transform the "non-places" of modernity into places of dispute and value.
Keywords: Homeless; Nonplace; COVID-19 Pandemic